Creative Reading in the Information Age: Paradoxes of Close and Distant Reading. (28th December 2017) - van de Ven, Inge
Abstract: This article reflects on transformations of modes of reading in an information age, asking what "creative reading" entails in information‐intensive, multimodal environments. We currently face the challenge of the development of reading strategies that oscillate between "close" and "distant" reading. For years, these reading strategies have been a topic of debate between practitioners of Digital Humanities on the one hand, and "traditional" humanists on the other. This ongoing polemics presents reading methods in an unnecessarily polarized manner. I argue that creativity research can be operationalized to come to a more productive model to characterize the ways we read in an information age. I show that the "schism" between close and distant reading is structured around a number of apparent paradoxes that I unravel such as hyper‐ and deep attention/attention and distraction, and convergence and divergence. The paradox of creativity resides in the fact that we find convergence in divergence and vice versa, that the two by definition intertwine. Building on these concepts, I propose a model that considers reading in terms of scale variance. I suggest the humanities turn to creativity research and the interrelations between divergent‐exploratory and convergent‐integrative thinking (Lubart), for a conceptual framework that will allow us to train students on all levels how to read (and how and when not to read), in an information age.